Characteristics of Parthenogenetic Stem Cells and Their Potential Treatment Strategy for Central Nervous System Diseases - Cai H; Huang J; Wang W; Lin W; Ahmed W; Lu D; Quan J; Chen L (Neuropsychiatric Disease and Treatment, 2025)
Hengsen Cai,1,* Jiajun Huang,2,* Wei Wang,2,* Wentong Lin,3,* Waqas Ahmed,4 Deng Lu,1 Jiewei Quan,1 Lukui Chen2 1Department of Neurosurgery, The second People’s Hospital of Pingnan, Pingnan, Guangxi, People’s Republic of China; 2Department of Neurosurgery, Southern Medical University Hospital of Integrated Traditional Chinese and Western Medicine, Southern Medical University, Guangzhou, 510310, People’s Republic of China; 3Department of Orthopaedics, Chaozhou Hospital of Traditional Chinese Medicine, Chaozhou, Guangdong, People’s Republic of China; 4Department of Neurology, Zhongda Hospital Southeast University, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lukui Chen, Department of Neurosurgery, Southern Medical University Hospital of Integrated Traditional Chinese and Western Medicine, Southern Medical University, Guangzhou, 510310, People’s Republic of China, Email neuro_clk@hotmail.comAbstract: Stem cells hold significant promise in treating neurological illnesses, such as stroke, spinal cord injury and neurodegenerative diseases. The origins and characteristics of human parthenogenetic stem cells might lead to a new research area in treating nervous system diseases. The current clinical studies in the field of traumatic brain injury and neurodegenerative diseases are reviewed. Some variables that influence common stem cells’ survival, proliferation, and therapeutic efficacy will be mentioned in this paper because they may play an important role in studying parthenogenetic stem cells.Keywords: parthenogenetic stem cells, neural stem cells, traumatic brain injury, spinal cord injury, neurodegenerative diseases, treatment strategy